Adaptación y caracterización morfológica de plantas medicinales subtropicales del cantón Echeandía, provincia de Bolívar - Borja Barragán, Carmen Elizabeth (2013)
The medicinal plants contribute to the invigoration of the programs of health and also to the economy of the Ecuador. They are different the forms in those that take advantage the plants an according space continue growing the world population. Most won't have access to the medications of the industry pharmacists. The present investigation was developed in the experimental farm Echeandía of the State University of Bolívar, canton Echeandía, province Bolívar, located to an altitude of 600 mls. They thought about the following objectives: i) Establish a bank germoplásmico of medicinal plants in the canton Echeandía. Ii) Identify and to characterize each one of the medicinal plants. iii) Create a database of plantsmedicinallyfor future investigations. It was used fifty species of subtropical medicinal plants to those that he/she was carried out a descriptive statistic being calculated Frequency (F), Percentage of the frequency (% f), arithmetic mean (Ẍ), Maxima (Max) and Minima (Min). The main results were: The morphological and agronomic characteristics of the plants medicinal employees in this investigationwere different for the main evaluated variables. Each species has a report of medicinal use, registered its family, names communes, scientific name including the gender. The variable height of plants, diameter of the shaft, wide equatorial of the leaf, number branches and leaves, longitude of the petiole was evaluated in a sample of 6 plants to the 45 days after the transplant and in the stage flotation fenológyc. Registered 100% of survival in the plants of medicinal. Inside the characterization they were herbaceous type species, arbustive, of pleasant aroma, with different types of leaves, flowers of showy colors, plants that can be cultivated to open field or in gavels, being able to multiply for seeds and vegetative parts. One had presence snails, same that was controlled on time in a manual way.